Mandibular alveolar bone volume in patients with different vertical facial dimensions - Thamer Alkhadra (Elsevier, 2017)
Objective: To evaluate if there is any difference in alveolar bone surface area in patients with high vertical facial dimension (long face), average vertical facial dimension (average face), and low vertical facial dimension (square short face). Materials and methods: Forty-five patients who had cone beam computed tomography (CBCT) as part of their orthodontic records were chosen according to their facial vertical dimension. Each group consisted of fifteen patients. Mandibular alveolar bone volume was calculated using Dolphin 3D Imaging software as the total surface area of the symphysis at the level of lower right canine to lower left canine and total surface areas for each patient was considered as total bone volume. Comparison was performed between groups using t-test. Results: Long face type patients showed higher bone volume (total surface area 3220 ± 368 mm2), average face patients have average bone volume (total surface area 2059 ± 620 mm2) while square short face patients have the lowest total bone volume (total surface area 1877 ± 112 mm2). There was a significant difference between long face and square short face groups (P < 0.005) however, there was no significant difference between long face and average face groups. Conclusions: Patients with long face type have higher mandibular alveolar bone volume compared to short facial type patients. Keywords: Alveolar bone volume, Mandibular symphysis, Facial types, Vertical dimension